PENDAPATAN USAHA PENGOLAHAN IKAN PADA KUB BINA SEJAHTERA DI KELURAHAN KANGKUNG KECAMATAN BUMI WARAS KOTA BANDAR LAMPUNG - Desi Darmilayanti; Muhammad Irfan Affandi; Rabiatul Adawiyah (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to find out the benefit level of fish processing unit in Bina Sejahtera KUB, Bandar Lampung.  This research uses a case study method, with descriptive data analysis by applying the formulation of economic evaluations consisting of revenue, Break Even Point (BEP), and R/C.  The results of this study indicate that the level of fish processing business income of KUB Bina Sejahtera both, over cash cost and total cost, are  >1 or profitable.  Key words: BEP, fish processing, KUB, marketing mix, R/C